Aaron Copland in Latin America : music and cultural politics - Hess, Carol A. (Music in American life., 2023)
"Between 1941 and 1963, Aaron Copland made four government-sponsored tours of Latin America that drew extensive attention at home and abroad. Interviews with eyewitnesses, previously untapped Latin American press accounts, and Copland's diaries inform Carol A. Hess's in-depth examination of the composer's approach to cultural diplomacy. As Hess shows, Copland's tours facilitated an exchange of music and ideas with Latin American composers while capturing the tenor of United States diplomatic efforts at various points in history. In Latin America, Copland's introduced works by U.S. composers, including himself, through lectures, radio broadcasts, live performance, and conversations. Back at home, he used his celebrity to draw attention to regional composers he admired. Hess's focus on Latin America's reception of Copland provides a variety of outside perspectives on the composer and his mission. She also teases out the broader meanings behind reviews of Copland and examines his critics in the context of their backgrounds, training, aesthetics, and politics"--